Reactualization Islamic Theology in Education: Designing Curriculum, Method Learning, and Technology Integration for Transformation Educative - Asep Abdullah; Qiqi Yuliati Zaqiah; Mohammad Ridwan; Sally Badriya Hisniati; Mahmud; Mohammad Erihardiana (Britain International for Academic Research (BIAR) Publisher, 2024)
The development of Islamic education has become the main focus of the effort to formulate return religious teachings to be more in accordance with the demands of the times and achieve transformation in system education. This article aims To explore How Islamic theology is actualized in the aspect of education, considering design curriculum, methods of learning, and integration technology. The method research used is qualitative analysis with studies of comprehensive library. Through a review of in-depth literature and articles, this identifies draft reactualization of Islamic theology in context education and explains the goals and approaches required to achieve it. Research results highlight the importance of the integration of values of Islamic theology in curriculum-relevant education with the demands of the times. Besides that, This review is about using interactive methods of learning, like discussion groups and technology, to facilitate a deep understanding of Islamic teachings. With the integration of Islamic theology in the curriculum, implementing method learning interactive, and utilising technology in a way that is wise and transformational, more educational , extensive and sustainable can achieved in Islamic education.